A large observational study of patients with primary immune thrombocytopenia receiving romiplostim in European clinical practice. (26th September 2016) - Steurer, Michael; Quittet, Philippe; Papadaki, Helen A.; Selleslag, Dominik; Viallard, Jean‐François; Kaiafa, Georgia; Janssens, Ann; Kozak, Tomas; Wadenvik, Hans; Schoonen, Marieke; Belton, Laura; Kreuzbauer, Georg
Abstract: Objective: Romiplostim has maintained long‐term platelet counts in patients with immune thrombocytopenia (ITP) for up to 5 yr in clinical studies. This prospective observational study aimed to describe romiplostim utilisation and outcomes in European clinical practice. Methods: Adults with primary ITP who received romiplostim in routine care were eligible. Results: Three‐hundred and forty patients were eligible for analysis, of whom 299 (88%) completed the 2‐yr observation period. The median age was 62 yr, with 43% of patients aged ≥65 yr, and two‐thirds of patients initiated romiplostim before splenectomy. The median average weekly dose of romiplostim was 2.8 μg/kg. The median baseline platelet count was 20 × 10 9 /L, which increased after 2 wk of romiplostim treatment and remained >50 × 10 9 /L thereafter. After romiplostim initiation, there was a decrease in rates of grade ≥3 bleeding events (from 12 to 2 per 100 patient‐years) and ITP‐related hospitalisations (from 87 to 33 per 100 patient‐years). The rate of thrombotic events was 2 per 100 patient‐years, and bone marrow fibrosis occurred in two patients. Conclusions: Romiplostim dosing, effectiveness and safety in an unselected real‐world ITP population seemed comparable with that observed in clinical studies.